Synchronous BALT Lymphoma and Squamous Cell Carcinoma of the Lung: Coincidence or Linkage? - Anastasia Oikonomou; Emanuelle Astrinakis; Ioannis Kotsianidis; Vassiliki Kaloutsi; Vassileios Didilis; Konstantinos Tsatalas; Panos Prassopoulos (Case Reports in Oncological Medicine)
A 72-year-old man presented with weight loss, fever, and malaise. Chest radiograph and CT revealed two large ill-defined masses in middle and left lower lobes. CT-guided biopsy of left lower lobe mass disclosed bronchus-associated lymphoid tissue (BALT) lymphoma. Middle lobe mass was considered second deposit in contralateral lung. The patient received chemotherapy for BALT. Followup CT disclosed regression of left lower lobe mass and stability of middle-lobe mass and of right paratracheal lymph nodes. CT-guided biopsy of middle-lobe mass revealed squamous cell lung carcinoma. Surgical biopsy of right paratracheal lymph nodes revealed malignancy. Disease was staged T3, N2, and M0. Combined chemotherapy for lung cancer and BALT lymphoma was initiated.